A site survey of damaged RC buildings in İzmir after the Aegean sea earthquake on October 30, 2020 - Halit Cenan Mertol; Gokhan Tunc; Tolga Akis (Građevinar)
An earthquake with a magnitude of Mw = 6.6 and a depth of approximately 16.5 km occurred on 30 October 2020 off the cost of Samos, a Greek island 35 km southwest of Seferihisar, a town in İzmir. The earthquake caused several collapses and severe structural damage in approximately 6,000 buildings, specifically in the Bayraklı District in İzmir Bay. This paper presents the observations and findings of a technical team that visited the earthquake-affected areas immediately after an earthquake. Eleven partially or fully collapsed buildings and several severely damaged reinforced concrete buildings were investigated. Based on the site observations, we observed that almost all of the collapsed or severely damaged reinforced concrete buildings in the region were built between 1975 and 2000. Site observations also confirmed that the construction of these collapsed or damaged buildings did not conform to the requirements outlined in the Turkish Earthquake Codes used at the time. The failures and severe damage to buildings in earthquake-affected areas are primarily related to inadequate reinforcement configuration, poor material quality, the absence of geotechnical studies, and framing problems related to their lateral load-carrying systems. Therefore, it is recommended that all the buildings located in and around İzmir Bay, particularly those built between 1975 and 2000, be structurally evaluated to prevent any further loss of life and property during future earthquakes.